Impacto de las barreras a la exportación en el desarrollo de Pymes agroexportadoras peruanas - Anton Pino, Melanie Rossana (2023)
Nowadays, many of the small and medium-sized companies in the agro-export sector are unable to expand their products in the international market because there are many types of export barriers that make this process difficult. According to Malca and Rubio (2015), there are four types of export barriers: procedural barriers, resource barriers, knowledge barriers, and exogenous barriers. This paper identifies different types of export barriers from the point of view of various authors, based on Oscar Malca. Likewise, previous studies carried out on SMEs around the world are analyzed, managing to observe the different situations that arise. In addition to this, different theories based on international trade are described, such as the Adam Smith theory, the Ricardian model, the Heckscher-Ohlin model, among others. Although there are previous studies on SMEs around the world, there are very few studies carried out on those within the Latin American territory that allow rethinking new policies or incentives that allow them to develop their growth. The results obtained shows that for the Peruvian agro-exporting SMEs surveyed, the lack of knowledge of the potential of export markets and/or the lack of knowledge of opportunities abroad is a knowledge barrier that should be given greater importance. The lack of technical personnel abroad and the company's insufficient production capacity are considered the most important resource barriers. Logistical difficulties and/or documentation and paperwork required are also identified as the most important procedural barrier. Finally, the exogenous barrier considered the most important by those surveyed is the exchange rate.